PKM Peningkatan Ketrampilan Pemasaran Digital Bagi Pelaku UMKM Ensikei Di Kota Kupang - Damaris Y. Koli; Febriana Inut; Florida Fahik (Jurnal Pengabdian Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) are one of the supporters of the economy in Indonesia, especially for the lower and middle class people. MSMEs have a strategic role in the government's efforts to overcome poverty and unemployment. One of the MSMEs that has developed in Kupang City is MSME Ensikei, this business started from a home-based business that produces and sells accessories and jewelry from local stones (muti) and also from woven materials with NTT motifs, as well as participating in marketing several products from other local craftsmen. such as: ginger sugar, VCO, fashion, bags and shoes with woven motifs in NTT. Responding to changes due to the COVID-19 pandemic, which resulted in sluggish sales, the easy way is to use digital marketing through social media. To improve the skills of using social media that are appropriate and useful, there needs to be regular training and mentoring for Ensikei MSMEs.